N-Body Simulation for Dark Matter Clustering at Different Epochs of the Universe - Brza, Mohamad Ali; Rasheed, Mariwan Ahmed (Al-Nahrain Journal of Science, 2013)
In this study the cold dark matter particles is simulated at different epochs of the universe using Gadget-2 code for lambda cold dark matter model (ΛCDM). Firstly, the dark matter particles distributed in homogenous form then with time because of the gravity effects the particles collected gradually to construct sub clumps of halo and then big clumps of halo. This process is shown in the simulation from redshift z17.7 (700Myr.) after the Big Bang of the universe to z0 (13.3Gyr.).During these epochs of the universe the clustering of dark matter halo, filaments, and voids are constructed. These clusters of halo which were found from the simulation are the basic parts of galaxy clusters.In the simulation also the velocity scale of each epoch shows the displacement of the dark matter particles at different directions to construct the halo.